Neuropsychiatric symptoms in Parkinson's disease: association with caregiver distress and disease severity. (24th June 2020) - Tsai, Wan-Chen; Lin, Hui-Chen; Chang, Chiung-Chih; Chang, Wen-Neng; Huang, Chih-Cheng; Cheng, Kuei-Yueh; Wang, Hung-Chen; Lin, Wei-Che; Hsiao, Sheng-Yuan; Lai, Yun-Ru; Lu, Cheng-Hsien; Tsai, Nai-Wen
ABSTRACT: Objectives: The condition of caregivers is important to the quality of care received by people with Parkinson's disease (PD), especially at the late disease stages. This study addresses the distress placed on caregivers by participants' neuropsychiatric symptoms at different stages of PD in Taiwan Methods: This prospective study enrolled 108 people with PD. All participants were examined with the Unified Parkinson's Disease Rating Scale (UPDRS), Neuropsychiatric Inventory (NPI), Mini-Mental State Examination (MMSE), Cognitive Abilities Screening Instrument (CASI), and Clinical Dementia Rating (CDR) scale. Caregiver distress was measured using the Neuropsychiatric Inventory Caregiver Distress Scale (NPI-D). Statistical analysis was used to explore the PD-related factors that contribute to caregiver distress. Results: The mean follow-up interval in the 108 PD participants were 24.0 ± 10.2 months with no participant lost to follow-up due to death. NPI-distress (the sum of NPI caregiver distress scale across the 12 domains of the NPI) was positively correlated with NPI-sum (the total score across the 12 domains of the NPI) ( r = 0.787, p < 0.001), CDR ( r = 0.403, p < 0.001), UPRDS ( r = 0.276, p = 0.004), and disease duration ( r = 0.246, p = 0.002), but negatively correlated with CASI ( r = −0.237, p = 0.043) and MMSE ( r = −0.281, p < 0.001). Multiple linear regression analysis showed that only NPI-sum and disease duration were independently correlated with NPI-distress. Conclusion: The disease duration and NPI-sum are independent predictors of caregiver distress in Taiwanese populations with PD. Early detection and reduction of neuropsychiatric symptoms in people with PD can help decrease caregiver distress.